Musculoskeletal Disorders among Dentists in Northwest area of the state of São Paulo, Brazil - Ana Carolina da Graça Fagundes Freire; Gabriella Barreto Soares; Tânia Adas Saliba Rovida; Cléa Adas Saliba Garbin; Artênio José Ísper Garbin (Universidade Estadual de Campinas, 2017)
Objective: To determine the prevalence of musculoskeletal disorders in dentists who attend postgraduate courses in various specialties and establish possible relationships with sociodemographic and occupational factors. Methodology: This is a cross-sectional study where 91 professionals responded to validated instruments: "Work-related activities that may contribute to job-related pain and / or injury" and NMQ "Nordic Musculoskeletal Questionnaire", and variables were also collected regarding sociodemographic and occupational characteristics. Results: WMSDs were often reported in the neck, shoulder, lower/upper back, and hand/wrists. Logistic regression analysis revealed that there was a correlation between reports of WMSD in lower back and work related (OR=13.40). Moreover, associations were found between WMSDs and the occupational factors that can contribute to musculoskeletal disorders. Conclusion: There was a high prevalence of musculoskeletal disorders among brazilian dentists, and that the work-related activities contributed to musculoskeletal disorders in dentists.